1989
DOI: 10.1084/jem.169.4.1233
|View full text |Cite
|
Sign up to set email alerts
|

Primary virus-induced lymphomas evade T cell immunity by failure to express viral antigens.

Abstract: It is well established that MHC-restricted T cell responses decisively influence the outcome of virus infection (1-3). In the rejection of murine leukemia virus-induced lymphomas, Th and cytotoxic T (Tc) t cells are considered essential effector cells, besides the effects of MuLVspecific antibodies, which can neutralize the virus and inhibit its spread (reviewed in reference 4). Many attempts have been made to characterize the viral antigens that are important in recognition by murine leukemia virus (MuLV)-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…molecules. Associative recognition of target cells by CTL depends on the expression of both class I MHC glycoproteins and foreign antigenic determinants on the target cells, therefore it seems reasonable to believe that modulation of either one is a potential mechanism of tumor escape from immune destruction [12,19,20,31,38,40]. Indeed, in acute measles virus infection of neuroblastoma cells, where the expression of H-2K molecules was down-regulated [21], down-regulation of H-2K was inversely correlated with measles virus antigen expression on the cell surface and was associated with decreased susceptibility to lysis by allospecific CTL.…”
Section: Discussionmentioning
confidence: 99%
“…molecules. Associative recognition of target cells by CTL depends on the expression of both class I MHC glycoproteins and foreign antigenic determinants on the target cells, therefore it seems reasonable to believe that modulation of either one is a potential mechanism of tumor escape from immune destruction [12,19,20,31,38,40]. Indeed, in acute measles virus infection of neuroblastoma cells, where the expression of H-2K molecules was down-regulated [21], down-regulation of H-2K was inversely correlated with measles virus antigen expression on the cell surface and was associated with decreased susceptibility to lysis by allospecific CTL.…”
Section: Discussionmentioning
confidence: 99%
“…RSV tumorigenesis is mediated by the oncogene v-src that, as an integral part of the retroviral genome, can continually spread to neighboring cells by reinfection, which facilitates progression of the tumors (Pontdn 1964). In addition, the products of viral replicative genes, namely env and gag, antigenically modify the infected cells and are responsible for an immune reaction against transformed cells (Poulin et al 1985;Vasmel et al 1989). However, we have demonstrated that only v-src flanked with the long terminal repeats (LTRs) can cause metastasizing tumor in hamsters (Svoboda et al 1983;Geryk et al 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Specific CTL recognition of tumor cells requires the presentation by MHC class I molecules of processed tumor antigen to the T lymphocyte antigen receptor. Tumor cell variants that escape CTL immunosurveiUance have been described (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). In most instances, the emergence of CTL escape variant cells is associated with the decrease or absence of MHC class I antigens required for antigen recognition by CTL (11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%